Design and energy analysis of a flywheel-based boom energy regeneration system for hydraulic excavators - Li, Jiansong; Li, Shaohui; Ji, Zhi; Wang, Yunfei (Frontiers in Energy Research, 2023)
The global energy crisis and growing environmental concerns provide a strong impetus for the development of fuel-efficient hydraulic excavators (HEs). The boom potential energy of a conventional HE is consumed by throttling in a lowering process, which is a major reason for energy inefficiency. To solve the issue, this paper presents a flywheel-based boom energy regeneration system for HEs using load-sensing systems. The otherwise wasted boom potential energy is regenerated by a pump/motor and stored in a flywheel. The recaptured energy is reused in the form of pressure energy released to the pump outlet. The energy efficiencies of a conventional load-sensing system and the proposed system were analyzed. A control strategy was proposed to optimize the energy-saving procedure. To obtain a more reliable simulation model, a coasting experiment of the flywheel was carried out to obtain the key parameters related to the friction of the flywheel. A 4-t HE in our laboratory was selected as a study case to investigate the energy-saving effect of the flywheel-based boom energy regeneration system. Numeric simulations showed that compared with a conventional load-sensing system, the energy-saving rate was about 32.7% in a typical digging and dumping cycle. These findings indicated that the flywheel-based boom energy regeneration system is promising for developing energy-efficient HEs.